Partisipasi Suami Dalam Pemberian Asi Eksklusif Di Desa Sentul Tanggulangin Sidoarjo: Husband's Participation In Exclusive Breast Milk In Sentul Tanggulangin Village, Sidoarjo - Hanum, Sri Mukhodim Faridah; Nurvitriana, Nidya Comdeca (Jurnal Kebidanan Midwiferia, 2015)
Exclusive breastfeeding is the best food to be given to the baby, because the contains all the nutrients needed by the baby. However, exclusive breastfeeding is still not much is done by mothers who have baby. Date of Health Office of Sidoarjo in 2012 of exclusive breastfeeding in Sidoarjo 51% of the target of 68.5%, while in the District Tanggulangin achievement still remain 58,8% ,and then the aim of this study was to analyze the relationship with the husband's participation Exclusive breastfeeding. Design research is an analytic survey with cross sectional approach. Obtained a sample of 32 respondents from 34 populations taken by simple random sampling. The present in the form of frequency tabulations and cross tabulations, to determine the relationship of the fisher's exact statistical test with significance level α = 0.05.Fisher's exact test research results for husband's participation obtained P (0.148)> α (0.05) so the Ho is accepted it means there is no relationship between participation husband with exclusive breastfeeding. The conclution of this study no association husband's participation with exclusive breastfeeding. Then the midwife advised to increase the frequency of counseling about the importance of exclusive breastfeeding for mothers and expectant mothers about the importance of exclusive breastfeeding.